2009
DOI: 10.1073/pnas.0909055106
|View full text |Cite
|
Sign up to set email alerts
|

aP2-Cre-mediated inactivation of acetyl-CoA carboxylase 1 causes growth retardation and reduced lipid accumulation in adipose tissues

Abstract: Adipose tissue is one of the major sites for fatty acid synthesis and lipid storage. We generated adipose (fat)-specific ACC1 knockout (FACC1KO) mice using the aP2-Cre/loxP system. FACC1KO mice showed prenatal growth retardation; after weaning, however, their weight gain was comparable to that of wild-type (WT) mice on a normal diet. Under lipogenic conditions of fasting/re-feeding a fat-free diet, lipid accumulation in adipose tissues of FACC1KO mice was significantly decreased; this is consistent with a 50 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 48 publications
3
51
0
1
Order By: Relevance
“…To test whether induction of cytosolic chaperones may be mediated by fat accumulation, we reduced expression of each of the major enzymes that are essential for fatty acid biosynthesis and evaluated the induction of cytosolic small heat shock protein hsp-16.2 expression. pod-2 RNAi, which targets the homolog of mammalian acetyl-coenzyme A (acetyl-CoA) carboxylase (acc1), is predicted to decrease malonyl-CoA, a substrate for fatty acid synthesis and a regulator of fatty acid β-oxidation, triglycerides (Mao et al, 2006), and lipid accumulation in adipose tissues (Mao et al, 2009). Reduced expression of the fatty acid synthase ( fasn ) fasn-1 is similarly predicted to reduce fatty acid biosynthesis, resulting in the accumulation of malonyl-CoA and inhibition of fatty acid β-oxidation (Fritz et al, 2013) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…To test whether induction of cytosolic chaperones may be mediated by fat accumulation, we reduced expression of each of the major enzymes that are essential for fatty acid biosynthesis and evaluated the induction of cytosolic small heat shock protein hsp-16.2 expression. pod-2 RNAi, which targets the homolog of mammalian acetyl-coenzyme A (acetyl-CoA) carboxylase (acc1), is predicted to decrease malonyl-CoA, a substrate for fatty acid synthesis and a regulator of fatty acid β-oxidation, triglycerides (Mao et al, 2006), and lipid accumulation in adipose tissues (Mao et al, 2009). Reduced expression of the fatty acid synthase ( fasn ) fasn-1 is similarly predicted to reduce fatty acid biosynthesis, resulting in the accumulation of malonyl-CoA and inhibition of fatty acid β-oxidation (Fritz et al, 2013) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…To bridge this gap in our knowledge, we generated conditional adipose tissue-specific Epac1 knockout mice using the transgenic Cre line driven by the adipocyte protein 2 (␣P2) gene promoter (16). Although ␣P2-Cre has been widely used for generating conditional adipose-specific knockout models, it has been reported that expression of ␣P2-driven Cre recombinase can be detected in macrophages (23) and brains (24) in certain instances. Therefore, in addition to confirming the knockdown of Epac1 in WAT, special attention was devoted to monitoring the expression levels of Epac1 in the hypothalamus and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation on AMPK-mediated regulation of osteoblast differentiation can be found in the study by Mao et al (45). They showed that aP2 (adipocyte protein 2)-Cre-mediated conditional KO of ACC1 results in reduced bone formation caused by defective osteoblastogenesis (45). ACC catalyzes a crucial step of the fatty acid synthesis pathway, and phosphorylation of ACC by AMPK inhibits the enzymatic activity of ACC (46).…”
Section: Discussionmentioning
confidence: 99%